Quand Argo argotise. Sur Svevo - Walter Geerts (Carnets)
A man's best friend, that is how dogs appear in literature. As such, they are conscious beings and they can speak. But in order to have a more trustworthy source of information on what his dog, Argo, can tell him on the animal species in general, Svevo's narrator learns the dog's own language. Svevo was indeed fascinated by darwinism. In his own unusual reading of the naturalist's view on human evolution, Svevo hypothesizes the existence of man – a small and highly vulnerable being that decides against all odds to walk upright – as a slave to a much more powerful animal who can protect him, the mammouth. And Argo's direct testimony from the animal world reveals just that. Argo, the animal, is just as selfish and hypocrite as the primitive human being carrying on in the shadow of the mammouth. And for all his evolutionist perfection, the human being itself has not changed, as Svevo abundantly illustrates through his literary characters, Zeno in the first place.